Return to Work in Driver with Diabetes Mellitus Type 2 on Oral Anti Diabetic with a History of Hypoglycaemia - Parmitasari; Dewi S. Soemarko; Muhammad Ikhsan Mokoagow; Nuri Purwito Adi (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: Patients with type 2 diabetes might be vulnerable to hypoglycemia, especially those treated with insulin secretagogues such as sulfonylurea and glinide, or insulin. Hypoglycemia compromises driving performance, causes slower response times, and reduces cognitive function. A return-to-work assessment needs to be done after a history of severe hypoglycemia or intractable episodes requiring hospitalization before resuming driving.Case presentation: A-44-year-old man, a commercial vehicle driver with a history of Oral antidiabetic drugs (OAD), was admitted to the hospital with severe hypoglycemia and pre-renal acute kidney failure. After being hospitalized for seven days, the patient was planned to be discharged and intended to return to work as a driver in a car rental company after recovery.Discussion: In determining return-to-work status, a proper analysis is needed in the form of seven steps to establish the return-to-work status. Job description, job demand, current medical status, disability, risk, and tolerance must be discussed before determining fit to work status. References related to how severe hypoglycemia relates to driving tasks could be valuable information in deciding fit-to-work status.Conclusion: Return-to-work assessment has concluded that the patient is temporarily unfit as a commercial vehicle driver for six weeks. Education regarding hypoglycemia, including recognizing symptoms early, how to treat promptly, and avoid further devastating accident should be discussed thoroughly between patient and physician. Close monitoring by Occupational Medicine Specialists in hypoglycemia state and symptoms as a return-to-work- program would be a valuable step.